A Meta‐analysis on the neural basis of planning: Activation likelihood estimation of functional brain imaging results in the Tower of London task. Issue 1 (15th September 2016) - Nitschke, Kai; Köstering, Lena; Finkel, Lisa; Weiller, Cornelius; Kaller, Christoph P.
Abstract: The ability to mentally design and evaluate series of future actions has often been studied in terms of planning abilities, commonly using well‐structured laboratory tasks like the Tower of London (ToL). Despite a wealth of studies, findings on the specific localization of planning processes within prefrontal cortex (PFC) and on the hemispheric lateralization are equivocal. Here, we address this issue by integrating evidence from two different sources of data: First, we provide a systematic overview of the existing lesion data on planning in the ToL (10 studies, 211 patients) which does not indicate any evidence for a general lateralization of planning processes in (pre)frontal cortex. Second, we report a quantitative meta‐analysis with activation likelihood estimation based on 31 functional neuroimaging datasets on the ToL. Separate meta‐analyses of the activation patterns reported for Overall Planning (537 participants) and for Planning Complexity (182 participants) congruently show bilateral contributions of mid‐dorsolateral PFC, frontal eye fields, supplementary motor area, precuneus, caudate, anterior insula, and inferior parietal cortex in addition to a left‐lateralized involvement of rostrolateral PFC. In contrast to previous attributions of planning‐related brain activity to the entire dorsolateral prefrontal cortex (dlPFC) and either its left or right homolog derived from single studies on the ToL, the present meta‐analyses stress the pivotal role specifically of the mid‐dorsolateral part of PFC (mid‐dlPFC), presumably corresponding to Brodmann Areas 46 and 9/46, and strongly argue for a bilateral rather than lateralized involvement of the dlPFC in planning in the ToL. Hum Brain Mapp 38:396–413, 2017 . © 2016 Wiley Periodicals, Inc.